Potential Tributyltin Chloride Degrading Marine Bacterium Alcaligene sp. 2-6 Strain S3 from Goa, India: Isolation and characterization of a potential TBTC degrader in the marine environment of Goa, India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Tributyltin chloride (TBTC) is used as antifoulants in ship hulls, boats, fishing nets, marine installations, aquaculture cages and docks to prevent settling of barnacles, seaweeds and tubeworms, finds its way finally into marine environment, resulting in negative impact on non-target organisms. Keeping these facts we have isolated and characterized a potential TBTC degrader from the sediments of Western India Shipyard Ltd. (WISL) in Murmugao Port Trust (MPT) harbor at Vasco-da-gama in Goa. This isolate was selected among five of the total 48 isolates screened, identified as Alcaligenes sp. 2-6 (Strain S3), tolerated 7mM TBTC, showed good growth at 5mM TBTC in Zobell marine broth (ZMB) and Mineral salts medium (MSM). It also showed cross tolerance to Cd2+, Hg2+ and As3+ ions, produced more exopolymer (EPS) and extracellular fluorescent pigment of phenazine type at 5mM TBTC. The TBTC degradation study revealed the presence of monobutyltin (MBT) within 45 days of incubation, acridine orange curing of bacterial cells revealed that genes conferring TBTC resistance and utilization are not plasmid borne. This isolate quickly adsorbs and slowly transforms TBTC, using dealkylation (debutylation) mechanism, in a stepwise fashion. Hence Alcaligenes sp. 2-6 (Strain S3), can be used in the bioremediation of TBTC contaminated sites of marine environment of Goa.